Linc00963 Promote Cell Proliferation and Tumor Growth in Castration-Resistant Prostate Cancer by Modulating miR-655/TRIM24 Axis - Bai, Minghua; He, Chenchen; Shi, Shengjia; Wang, Mincong; Ma, Jinlu; Yang, Pengtao; Dong, Yiping; Mou, Xingyi; Han, Suxia (Frontiers in Oncology, 2021)
Previous studies have shown that both long intergenic non-coding RNA 00963 (Linc00963) and tripartite motif containing 24 (TRIM24) are activators of the PI3K/AKT pathway, and both are involved in the carcinogenesis and progression of prostate cancer. However, the regulatory mechanisms between Linc00963 and TRIM24 are still unclear. In this study, we aimed to elucidate the underlying relationship between Linc00963 and TRIM24 in castration-resistant prostate cancer (CRPC). We found that TRIM24, an established oncogene in CRPC, was positively correlated with Linc00963 in prostate cancer tissues. In addition, TRIM24 was positively regulated by Lin00963 in CRPC cells. Mechanistically, TRIM24 was the direct target of microRNA-655 (miR-655) in CRPC cells, and Linc00963 could competitively bind miR-655 and upregulate TRIM24 expression. Using gain- and loss-of- function assays and rescue assays, we identified that miR-655 inhibits TRIM24 expression and cell proliferation and colony forming ability in CRPC, and that Linc00963 promotes TRIM24 expression, cell proliferation, and colony forming ability of CRPC cells by directly suppressing miR-655 expression. We further identified that Linc00963 could promote tumor growth of CRPC cells by inhibiting miR-655 and upregulating TRIM24 axis in vivo. Taken together, our study reveals a new mechanism for the Linc00963/miR-655/TRIM24 ceRNA network in accelerating cell proliferation in CRPC in vitro and in vivo, and suggests that Linc00963 could be considered a novel therapeutic target for CRPC.